Prevention of Cybercrime through the Development of Criminal Responsibility Principles for Internet Users - Raharjo, Agus (Faculty of Law, Universitas Jenderal Soedirman, 2021)
There is no guarantee of security in cyberspace. Cybercrime is the use of computer technology for illegal activities. Cybercrime ignores territory, and can even become an automatic crime according to the nature of the machine. The crime prevention model, which has been more reactive and only suitable for the real world, is not an effective way to deal with cybercrime. This research is normative legal research, with the main data source in the form of secondary data. Hacking is an illegal activity that takes many victims and its handling is not complete. The difficulty that arises is the issue of jurisdiction because perpetrators and victims are often in different jurisdictions. Although legal instruments have adopted provisions on the principle of ubiquity, in practice it is not as easy as imagined. The Bangkok International Summit (2007) invites countries to promote cyber security by increasing and developing international global partnerships to prevent, detect, and cybercrime, but this has not been implemented properly. For this reason, it is necessary to develop the principle of criminal responsibility which can be an incentive in overcoming cybercrime.Keywords: cybercrime; hacking; ubiquity; criminal responsibility